2012
DOI: 10.1007/s00300-012-1256-6
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of ciliates on Ecology Glacier (King George Island, Antarctica): relationships between species assemblages and environmental parameters

Abstract: Ciliates are important consumers of pico-and nano-sized producers, are nutrient regenerators, and are an important food source for metazoans. To date, ecological research on ciliates has focused on marine ecosystems rather than on glacier habitats. This paper presents the first major study on ciliates from the Ecology Glacier (South Shetland Islands, Antarctica). The objective of the study was to investigate the structure and spatial distribution of ciliate communities and to identify the environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Recent morphological and molecular studies have shown that glacial systems harbour a high microbial diversity including particle‐associated ciliate groups among others (Anesio & Laybourn‐Parry, ; Mieczan et al ., ; Lazzaro, Risse‐Buhl & Brankatschk, ; Lutz et al ., ). In our studied lakes, the species richness is significantly higher in the glacial turbid Lake FAS 3 than in the clear Lake FAS 4.…”
Section: Discussionmentioning
confidence: 99%
“…Recent morphological and molecular studies have shown that glacial systems harbour a high microbial diversity including particle‐associated ciliate groups among others (Anesio & Laybourn‐Parry, ; Mieczan et al ., ; Lazzaro, Risse‐Buhl & Brankatschk, ; Lutz et al ., ). In our studied lakes, the species richness is significantly higher in the glacial turbid Lake FAS 3 than in the clear Lake FAS 4.…”
Section: Discussionmentioning
confidence: 99%
“…Many Archaea, bacteria, cyanobacteria, algae, fungi, ciliates and microinvertebrates (rotifers, tardigrades, arthropods etc.) have been reported from almost all investigated glaciers (for example Mieczan and others 2013a, 2013b; Sheridan and others 2003; Singh and others 2014b, 2014c; Takeuchi and Koshima 2004; Zawierucha and others 2015). These glaciers and ice sheets should be regarded as independent biomes due to truncated food webs and distinct biogeographical structure, with the cryoconite holes as autonomous microecosystems (Anesio and Laybourn-Parry 2012; Wharton and others 1985).…”
Section: Introductionmentioning
confidence: 85%
“…Mieczan and others (2013b): Antarctica: a) King George Island, Ecology Glacier [ 62°10.226′S, 58°28.268′W/ 62°10 ′ 13”S, 58°28’16”W –62°10.404′S, 58°28.546′W/ 62°10 ′ 24”S, 58°28 ′ 33” W; 40–145 m asl ].…”
Section: List Of Localitiesmentioning
confidence: 99%
“…Currently, cryoconite holes are considered to be extreme microecosystems, where primary production could be similar to those in the soil, and microorganisms such as bacteria, ciliata or algae inhabiting these environments (e.g. Vincent et al ., ; Mueller et al ., ; Fountain et al ., ; Hodson et al ., ; Anesio et al ., ; Cameron, Hodson & Osborn, ; Mieczan et al ., ). The development and functioning of these habitats are possible because of a decrease in albedo on the surfaces of cryoconite‐covered glaciers (e.g.…”
Section: Introductionmentioning
confidence: 97%